Report of the Working Group on Atlanto Scandian Herring ... - ICES (ICES Expert Group reports (until 2018), 2023)
At its Statutory Meeting in Copenhagen 1978, the International Council for the Exploration of the Sea (ICES) decided that the Atlanto-Scandian Herring Working Group should meet at the ICES headquarters for three days during the week 21-26 May 1979 to assess the state of the Atlanto-Scandian herring (Chairman: Mr. J. Jakobsson). The Group should also evaluate all available evidence on the relation of the capelin at Jan Mayen with neighbouring stocks. ...